A clinical case of gunshot shrapnel penetrating wound of the chest with injury to the inferior vena cava with migration of a foreign body along the blood stream - Tsumbaliuk, V. I.; Lurin, I. A.; Makarov, V. V.; Nehoduiko, V. V.; Buchnieva, O. V.; Tertyshnyi, S. V.; Bunin, Y. V. (Zaporozhye Medical Journal, 2022)
Damage to the major vessels in a retroperitoneal trauma belongs to the category of the most difficult, including damage to the inferior vena cava. The aim of the work is to demonstrate the features of clinical manifestations and tactical solutions of a gunshot fragment blind wound of the inferior vena cava with the migration of a foreign body along the blood stream. Materials and methods. A case of a gunshot fragment wound of the inferior vena cava with migration of the foreign body along the blood stream was studied. An injured person underwent sCT with and without contrast, FAST protocol, general blood test, biochemical blood test, CBV was determined using the formula of Moore, hourly diuresis was measured. Results. The patient was operated on for vital signs, the condition of the injured person was stabilized. During the revision of the abdominal cavity and paranephric tissue, no foreign body was identified. In the immediate postoperative period, the injured person underwent chest and abdominal CT, according to the data of that, a metal fragment was identified, which migrated along the inferior vena cava to the point of connection with the right atrium. The injured man was operated on at another specialized facility, where the foreign body was removed using a surgical magnetic tool. Conclusions. Fire damage to the inferior vena cava is classically accompanied by a severe general condition, massive blood loss, which requires urgent surgical interventions. Multi-component preoperative preparation, a clearly established diagnostic plan, a multidisciplinary approach based on the example of our clinical case allow saving life even in the most complex cases.